Analisis Manajemen Mutu pada Industri Garment: Narrative Literature Review - Rizky Fathia Della Khoirunisa; Ragita Octavia (Journal of Information Systems and Management (JISMA), 2023)
Quality control is very important in producing an item to maintain the stability of the quality of production results and as one of the efforts to find unexpected factors that cause a lack of smooth functioning in a production process so that if there is a disturbance, corrective action can be taken immediately before there are too many non-conforming products. with production. The garment production control process is usually carried out by checking all departments in order to minimize defects in production. The result of this activity is the implementation of quality control in every activity of producing clothes, starting from procuring raw materials to finishing activities. With the implementation of quality management and quality control in every production activity in the garment business, it is expected to minimize disruptions or defective products so that the products produced can be in accordance with consumer demand.